China's e-junkies head for rehab [Internet addicts treatment]. - Lin-Liu, J. (IEEE spectrum)
This paper reports on the growing problem of Internet addiction among Chinese teenagers. The problem has become so widespread that an Internet addiction center has been established at the Beijing Military Clinic where Internet addicts can be treated with a combination of counseling, physical activity, antidepressants and even electrical treatments. The lack of open space for sports and recreation due to the crowded urban environment is seen as the major contributor to the problem.